2004
DOI: 10.1038/sj.bjc.6602188
|View full text |Cite
|
Sign up to set email alerts
|

S100A2 is strongly expressed in airway basal cells, preneoplastic bronchial lesions and primary non-small cell lung carcinomas

Abstract: S100A2 gene products were shown to be frequently and dramatically over-represented in non-small cell lung cancer (NSCLC) lesions over normal tissue by microarray analysis. We have now analysed an independent series of NSCLC tumours and multiple matched normal bronchial epithelial sites by RT -PCR and immunohistochemistry to investigate: whether this expression pattern can be confirmed and whether elevated expression is associated with tumour histology, clinical outcome or preneoplasia. In this second series, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
5
41
1
Order By: Relevance
“…High expression of S100A2 is associated with metastasis and predicts survival in early stages of NSCLC. These findings are supported by studies in a mouse model of non-small cell lung cancer (NSCLC) where NOD/SCID mice xenografted with NSCLC cells overexpressing S100A2 demonstrated significantly more metastases than vector alone transfected cells (Heighway et al, 2002;Diederichs et al, 2004;Smith et al, 2004;Wang et al, 2005;Zech et al, 2006;Bartling et al, 2007;Bulk et al, 2009;Strazisar et al, 2009a;Strazisar et al, 2009b).…”
Section: Notesupporting
confidence: 62%
“…High expression of S100A2 is associated with metastasis and predicts survival in early stages of NSCLC. These findings are supported by studies in a mouse model of non-small cell lung cancer (NSCLC) where NOD/SCID mice xenografted with NSCLC cells overexpressing S100A2 demonstrated significantly more metastases than vector alone transfected cells (Heighway et al, 2002;Diederichs et al, 2004;Smith et al, 2004;Wang et al, 2005;Zech et al, 2006;Bartling et al, 2007;Bulk et al, 2009;Strazisar et al, 2009a;Strazisar et al, 2009b).…”
Section: Notesupporting
confidence: 62%
“…27 Recent investigations have emphasized the potential diagnostic and oncogenetic role of S100 proteins in a variety of tumors. [28][29][30][31][32][33][34] In this study, we found that S100A1 protein is expressed in renal oncocytomas, and in clear cell and papillary renal cell carcinomas but not in chromophobe renal cell carcinomas. We found significant statistical differences between S100A1 immunoexpression in clear cell and chromophobe renal cell carcinomas (Po0.001), which suggests that S100A1 could be a useful tool in their differential diagnosis.…”
Section: Discussionmentioning
confidence: 73%
“…The S100A2 gene is significantly differently expressed in ADC versus SCC, an observation that had already been detected with IHC and RT-PCR in 2004 by Smith et al [38]. Many discrepancies in the results concerning S100A2 expression have arisen: it was stated that the gene is down-regulated in NSCLC, while further research showed that its expression levels depend on the stage of the NSCLC, and that in the main, S100A2 is over-expressed in lung cancer tumours.…”
Section: Discussionmentioning
confidence: 89%
“…In the most recent studies, it was proposed that over-expression of the S100A2 gene in stage I NSCLC indicates a poor prognosis, and may be used to identify patients with early-stage NSCLC [39], or even as a predictor of distant metastasis [40]. There could also be differences in the levels of expression according to the NSCLC type [38]. We present here data on the COX-2, hTERT, MDM2, LATS2 and S100A2 expression levels in NSCLC, and how they relate to the NSCLC type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation